Concomitant oral and intravenous pharmacokinetics of trametinib, a MEK inhibitor, in subjects with solid tumours. (September 2014) - Leonowens, Cathrine; Pendry, Carolyn; Bauman, John; Young, Graeme C.; Ho, May; Henriquez, Frank; Fang, Lei; Morrison, Royce A.; Orford, Keith; Ouellet, Daniele
<x xml:space="preserve">Abstract</x> Aims The aim of this phase 1, single centre, open label study in four patients with solid tumours was to determine the absolute bioavailability of a 2 mg oral dose of trametinib. Trametinib is an orally bioavailable, reversible and selective allosteric inhibitor of MEK1 and MEK2 activation and kinase activity. Methods A microtracer study approach, in which a 5 μg radiolabelled i.v. microdose of trametinib was given concomitantly with an unlabelled 2 mg oral tablet formulation, was used to recover i.v. and oral pharmacokinetic parameters, simultaneously. Results The least‐squares mean (90% confidence interval) absolute bioavailability of trametinib (2 mg tablet) was 72.3% (50.0%, 104.6%). Median tmax after oral administration was 1.5 h and the geometric mean terminal half‐life was 11 days. The geometric mean clearance and volume of distribution after i.v. administration were 3.21 l h−1 and 976 l, respectively, resulting in a terminal elimination half‐life of 11 days. Conclusions Trametinib absolute bioavailability was moderate to high, whereas first pass metabolism was low.